Improving Students' Analytical Thinking Skills by Using the Discovery Learning Model in Islamic Education Learning at SMA Negeri 2 Rantau Selamat - T Yusrizal (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students’ analytical thinking skills through the implementation of the Discovery Learning model in Islamic Education learning at SMA Negeri 2 Rantau Selamat. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 32 eleventh-grade students in the 2025/2026 academic year. Data were collected through analytical thinking tests, observation sheets, and documentation. Quantitative data were analyzed using descriptive statistics and normalized gain (N-gain), while qualitative data were analyzed through thematic reflection. The findings indicate a significant improvement in students’ analytical thinking skills after the implementation of the Discovery Learning model. The mean pre-cycle score was 62.45, categorized as low. After Cycle I, the mean score increased to 74.18 with 68.75% of students achieving the minimum mastery criterion (MMC). In Cycle II, the mean score further increased to 86.03, with 90.63% of students meeting the MMC. The N-gain score of 0.64 indicates a moderate-to-high improvement category. Observational data also revealed enhanced student engagement, critical questioning, collaborative problem-solving, and the ability to formulate evidence-based conclusions. These results demonstrate that the Discovery Learning model effectively fosters analytical thinking skills in Islamic Education learning contexts. The model encourages active exploration, hypothesis formulation, data analysis, and reflective reasoning aligned with higher-order thinking competencies. This study contributes empirical evidence supporting the integration of student-centered learning models in Islamic Education to promote 21st-century analytical competencies. Future research may expand the scope by employing quasi-experimental designs and involving multiple schools to enhance generalizability.